SOCIAL AND ECONOMIC BURDEN OF FIVE NATURAL FOCAL INFECTIONS IN THE RUSSIAN FEDERATION - A. E. Platonov; N. A. Avksentyev; M. V. Avksentyeva; E. V. Derkach; O. V. Platonova; A. V. Titkov; N. M. Kolyasnikova (IRBIS LLC, 2015)
Study objective: to perform assessment of the social and economic burden (analysis of the cost of disease) of five natural focal transmitted infectious diseases in theRussian Federationon the whole and in certain regions: ixodic tick-borne borreliosis, Siberian tick-borne typhus,Astrakhanrickettsial fever, Crimean hemorrhagic fever, andWest Nileencephalitis. Materials and methods. Direct and indirect costs caused with the studied diseases and the number of lost Disability Adjusted Life Years (DALY) are calculated in the probability model. Results. The total value of social and economic losses associated with vector-borne infectious diseases comprised 909 million rubles in prices of 2011; most of the value is represented with ixodid tick-borne borreliosis. Totally, these diseases cause the loss of 16,599 DALY.